Holistic tool for ecosystem services and disservices assessment in the urban forests of the Real Bosco di Capodimonte, Naples - Antonello Prigioniero; Bruno Paura; Daniela Zuzolo; Maria Tartaglia; Alessia Postiglione; Pierpaolo Scarano; Sylvain Bellenger; Anna Capuano; Eva Serpe; Rosaria Sciarrillo; Carmine Guarino (Scientific Reports, 2022)
Abstract A tool for urban forest Ecosystem services (ES) and disservices (ED) assessment has been developed to visualize (i) overall ES and ED value, (ii) ES–ED trade-off and (iii) explore principal influences in ES and ED provision. The Real Bosco di Capodimonte (RBC) (Naples, Southern Italy) has been chosen as a case study. ES and ED linked to urban forest plant cover were: biodiversity, carbon storage, gross and net carbon sequestration, lessen runoff, oxygen production, air pollution removal, UV effects reduction, pollen-related allergenicity risk, and volatile organic compounds (VOCs) emissions. A phytosociological survey was conducted and biodiversity value was evaluated. ES and ED were assessed by i-Tree Eco model and Index of Urban Green Zones Allergenicity (IUGZA). Results showed that 441 different plant species occur in the RBC and the most represented genera are Quercus and Trifolium, while the largest family was Asteraceae. Carbon storage and pollution removal were highest in natural forest, while remaining ES were greater in managed forest areas. Highest value for VOCs emission and allergenicity were assigned to managed and natural forest, respectively. Managed forest scored the highest ES–ED value, while managed grassland scored the lowest. Results highlighted the greater influence of plant cover structure in overall ES and ED provision levels, and management influence considering the same type of plant cover. The model could be a valuable tool for ES and ED effective management generally applicable in urban forests.